The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1651-2227.1996.tb18227.x
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual development of offspring of diabetic mothers

Abstract: Intellectual development of offspring of diabetic mothers. Acta Pzdiatr 1996;85: 1 192-6. Stockholm. ISSN 0803-5253 We prospectively evaluated the intellectual development of 33 children who were born to 33 diabetic Japanese mothers and compared them to 34 children born to non-diabetic mothers (controls) during the same period at Kurume University Hospital between 1987and i 989. Birthweight, maternal ageand the infant's age at the time of intelligence testing did not differ significantly between the offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 5 publications
2
33
0
Order By: Relevance
“…It has been suggested by some investigators that offspring born to either mothers with PDM or GDM are more likely to have poorer cognitive and language development than those born to nondiabetic mothers. [28][29][30][31][32][33] However, other investigators have either found no such associations 17,18,20,22 or report contradictory findings. 23 To the best of our knowledge, systematically synthesized information on the associations between maternal diabetes during pregnancy and offspring's cognitive development, particularly in childhood, is lacking.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…It has been suggested by some investigators that offspring born to either mothers with PDM or GDM are more likely to have poorer cognitive and language development than those born to nondiabetic mothers. [28][29][30][31][32][33] However, other investigators have either found no such associations 17,18,20,22 or report contradictory findings. 23 To the best of our knowledge, systematically synthesized information on the associations between maternal diabetes during pregnancy and offspring's cognitive development, particularly in childhood, is lacking.…”
mentioning
confidence: 68%
“…Therefore, we included Nelson et al 32 (ie, better sample size and relatively recent) and Townsend et al 22 (ie, cognitive development was measured at the age of 4 years by using the Wechsler Intelligence Scale for Children) in the review. Overall, 14 studies [16][17][18][19][20][21][22][23][28][29][30][31][32][33] were eligible for the present review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations